2005
DOI: 10.1038/sj.gt.3302671
|View full text |Cite
|
Sign up to set email alerts
|

A membrane antibody receptor for noninvasive imaging of gene expression

Abstract: Monitoring gene expression is important to optimize gene therapy protocols and ensure that the proper tissue distribution is achieved in clinical practice. We developed a noninvasive imaging system based on the expression of artificial antibody receptors to trap hapten-labeled imaging probes. Functional membrane-bound anti-dansyl antibodies (DNS receptor) were stably expressed on melanoma cells in vitro and in vivo. A bivalent (DNS) 2 -diethylenetriaminepentaacetic 111 Indium probe specifically bound to cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…40 The plasmids were i.v. injected in 2 ml PBS within 8 s for hydrodynamicbased gene transfer on days 1 and 8.…”
Section: Mbg Immunogenicitymentioning
confidence: 99%
“…40 The plasmids were i.v. injected in 2 ml PBS within 8 s for hydrodynamicbased gene transfer on days 1 and 8.…”
Section: Mbg Immunogenicitymentioning
confidence: 99%
“…We previously showed that DNS receptors can specifically trap a bivalent (DNS) 2 -dithylenetriaminepentaacetate-111 Indium ((DNS) 2 -DTPA-111 In) probe in mice, as assessed by gamma camera imaging. 11 These results suggest that multimodality imaging (MR, optical and gamma camera imaging) can be employed to monitor DNS receptors in vivo by choosing the proper DNS probe.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported a novel gene/probe imaging system based on the expression of anti-DNS (5-dimethylamino-1-naphthalene sulfonic acid) single-chain antibody receptors (DNS receptor) on cells to trap DNS-derivatized imaging probes to assess the location, extent and persistence of gene expression in live animals. 11 We showed that a bivalent (DNS) 2 -diethylenetriaminepentaacetate-111 Indium ((DNS) 2 -DTPA- 111 In) probe could specifically localize to DNS receptors on B16/F1 tumors in mice as assessed by gamma camera imaging. 11 However, an analogous gadolinium probe ((DNS) 2 -DTPA-Gd (III)) could not be detected by MR imaging due to poor sensitivity (unpublished results).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations